Long-term clinical course and prognosis of hot water epilepsy: 15-Year follow-up - Balgetir, Ferhat; Gonen, Murat; Mungen, Eren; Berilgen, Ayse; Mungen, Bulent (Academic Press Inc Elsevier Science, 2022)
Objective: Hot water epilepsy (HWE) is a type of reflex epilepsy triggered by bathing with hot water. Hot water epilepsy is generally considered as a self-limiting benign disease although its long-term course and prognosis remains unknown. In this study, we aimed to determine the long-term clinical course and prognosis of hot water epilepsy and possible factors affecting them. Methods: The diagnosis of HWE was made based on the clinical history obtained from patients and their first degree relatives witnessing to the seizures and video recordings of seizures if available; then, the type of seizure was identified. Good prognosis was defined as patients whose seizures were controlled with or without preventive measures and who did not require antiepileptic treatment. The poor prognosis was defined as patients whose seizures continued despite preventive measures and required antiepileptic treatment. Results: The study included 50 (31 male and 19 female) patients with a mean follow-up of 17.63 +/- 10.46 (median, 15.0) years. The age at onset of seizure was 14.52 +/- 12.71 (median: 10.0) years. There were 38 (76%) patients in the good prognosis group. 18 (36%) of them achieved complete remission, who did not require preventive measures. In the remaining 20 (40%) patients, seizures could be controlled with only preventive measures. Seizures could be controlled with antiepileptic treatment in only 1 (2%) of 12 (24%) patients in the poor prognosis group. A significant relationship was found between the frequency of hot water seizures (HWSs) and poor prognosis (p = 0.019), as well as the presence of spontaneous seizures outside of bathing and poor prognosis (p = 0.000). Significance: Hot water epilepsy, as previously known, is not a self-limiting benign disease. Approximately 3/4 of the cases have a good prognosis, but the rest are in the case of chronic epilepsy. The low response rate to antiepileptics' treatment suggests that the pathogenesis of the HWE may differ from other epilepsies. (C) 2022 Elsevier Inc. All rights reserved.
Keywords: Hot water epilepsy; Reflex epilepsy; Prognosis